2014
DOI: 10.3329/sja.v11i1.18390
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil conservation techniques on growth and yield of maize (Zea mays L.) in Terai region of West Bengal

Abstract: The climate of the terai region of West Bengal, India in general, is subtropical par humid to tropical with light textured acid soil with the problems like low moisture retention, low water use efficiency, leaching of bases, soil erosion, limited availability of multiple plant nutrients and restricted activity of beneficial soil micro-organisms. To combat these soil health related problems and to improve the overall productivity of North Bengal, a comparison between the conventional and conservation tillage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
3
0
0
Order By: Relevance
“…11,18 and 19 The growth parameters such as dry matter accumulation, LAI and CGR were higher on irrigated plots compared to the other plots. This finding is also in conformity with the findings of De and Bandyopadhyay 20 and Yi et al, 21 . ).…”
Section: Results and Discussion Physiological Parameterssupporting
confidence: 93%
“…11,18 and 19 The growth parameters such as dry matter accumulation, LAI and CGR were higher on irrigated plots compared to the other plots. This finding is also in conformity with the findings of De and Bandyopadhyay 20 and Yi et al, 21 . ).…”
Section: Results and Discussion Physiological Parameterssupporting
confidence: 93%
“…Reduction in recommended dose of fertilizer beyond 75% resulted in significantly lower yields. Slow organic matter decomposition through changes in nutrient mineralization/immobilization improved the soil fertility and the potential nutrient supply to the growing cultivated crops (De and Bandyopadhyay, 2013). The results are in confirmatory of the findings by Sharma et al, 2007 andDe et al, 2009. From pooled data of three years (table 2) it is depicted that days to 1 st flowering and 50% flowering (days) were found to be differs non-significantly for liming, molybdenum seed treatment and different levels of recommended dose.…”
Section: Growth and Flowering Characterssupporting
confidence: 87%
“…They differ significantly from R 100 over R 0 by 87.11 and 66.58 % in case of grain yield and stick yield keeping the reason behind it the same as earlier one. Confirmations are obtained from the results of findings by Sharma et al, 2010 andBandyopadhyay, 2013. From the polynomial curve fitting (Figure 1 and 2), it showed that with the increase in fertilizer doses beyond 75 kg ha -1 , increase in grain yield was achieved but with decreasing rate at liming @ 150 and 200 kg ha -1 with treated seeds whereas non-treated seeds showed some deviation which might be due to direct or indirect effect of molybdenum with liming.…”
Section: Yield Characterssupporting
confidence: 73%